Reproductive Biology of One-Stripe Spiny Eel, Macrognathus aral (Bloch and Schneider, 1801) - Das, Manas; Bhanja, Avik; Mandal, Sayan; Maity, Joydev; Mandal, Basudev (Hasanuddin University, 2024)
The present study provides important details on the reproductive biology of Macrognathus aral. A comparison of the one-stripe freshwater spiny eel's reproductive biology, including sexual dimorphism, sex ratio, length at first sexual maturity, gonadal maturation, gonadosomatic index, and fecundity, was made. During the breeding season, both sexes show sexual differentiation in body colour, males have dorsally brown, and ventrally whitish-yellow and females have dorsally yellowish-brown and ventrally yellowish body colours, which allows for sexual dimorphism. The male-to-female sex ratio was verified to be 1:0.72 (p < 0.05) by the Chi-square test (χ2). 50% of males and females attained their first sexual maturity at 17.5-19.4 cm and 19.5-22.4 cm respectively. The gonado somatic index value in males and females was highest in the same month of July i.e., 1.95 ± 0.19 and 14.51 ± 0.81respectively. The month of July had the highest number of stage IV gonads, which was a sign of spawning. The absolute fecundity ranged from 3312 ± 34.23 to 12321 ± 299.85, with an average value of 6822.56. The correlation coefficient of fecundity with total length (0.9297), body weight (0.8539), and gonad weight (0.9640) were highly significant (p < 0.05).